2021
DOI: 10.1002/aenm.202100925
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Pre‐Lithiation of Silicon/Graphite Negative Electrodes in “Dry State” and After Electrolyte Addition Using Passivated Lithium Metal Powder

Abstract: Because of its high specific capacity, silicon is regarded as the most promising candidate to be incrementally added to graphite‐based negative electrodes in lithium‐ion batteries. However, silicon suffers from significant volume changes upon (de‐)lithiation leading to continuous re‐formation of the solid electrolyte interphase (SEI) and ongoing active lithium losses. One prominent approach to compensate for active lithium losses is pre‐lithiation. Here, the “contact pre‐lithiation” of silicon/graphite (Si/Gr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 51 publications
(65 reference statements)
0
49
0
Order By: Relevance
“…It is also reported that Li 2 CO 3 protects lithium from reaction with all atmospheric gases except H 2 O. 45 Consequently, this passivation layer must have been at least partly destroyed for the samples which tarnished and reacted with nitrogen forming Li 3 N. To verify this, we prepared a bunch of samples through tearing and ripping instead of controlled slicing to destroy the passivation layer on purpose. In most cases, the samples prepared in this way reacted to Li 3 N.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that Li 2 CO 3 protects lithium from reaction with all atmospheric gases except H 2 O. 45 Consequently, this passivation layer must have been at least partly destroyed for the samples which tarnished and reacted with nitrogen forming Li 3 N. To verify this, we prepared a bunch of samples through tearing and ripping instead of controlled slicing to destroy the passivation layer on purpose. In most cases, the samples prepared in this way reacted to Li 3 N.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As lithium hydroxide and carbonate form a stable and well-covering passivation layer according to their PBRs, lithium foils covered with these compounds appear to be protected against reaction with nitrogen. It is also reported that Li 2 CO 3 protects lithium from reaction with all atmospheric gases except H 2 O . Consequently, this passivation layer must have been at least partly destroyed for the samples which tarnished and reacted with nitrogen forming Li 3 N. To verify this, we prepared a bunch of samples through tearing and ripping instead of controlled slicing to destroy the passivation layer on purpose.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Another method for investigating lithium deposition during cycling is insitu observation using special cell holders. Insitu observations in the ECC-Opto Stud, manufactured by EL-Cells GmbH (Hamburg, Germany), on battery cells were made in [26][27][28][29][30][31][32][33] using Raman spectroscopy, X-ray diffraction (XRD) and optical analytics. Observations were made using Raman spectroscopy [27,31,32] and XRD [26,28,33] to observe changes in electrodes and SEI during aging.…”
Section: Future Workmentioning
confidence: 99%
“…Insitu observations in the ECC-Opto Stud, manufactured by EL-Cells GmbH (Hamburg, Germany), on battery cells were made in [26][27][28][29][30][31][32][33] using Raman spectroscopy, X-ray diffraction (XRD) and optical analytics. Observations were made using Raman spectroscopy [27,31,32] and XRD [26,28,33] to observe changes in electrodes and SEI during aging. Merryweather et al [29] used the above-mentioned cell housing for optical interferometric scattering measurements to detect single-particle ion dynamics, and Rittweger et al [30] observed the reflectivity of cathodes during charge and discharge.…”
Section: Future Workmentioning
confidence: 99%
“…After crack formation on the intrinsic SEI, the side reactions continue, leading to further consumption of Li and electrolyte, which results in low Coulombic efficiency (CE) and rapid capacity decay. 2,20,23,24 In previous reports, focusing on the volume variation, various strategies have been employed in anode material designs, such as nanowires, 25,26 nanofibers, 27,28 nanotubes, 29,30 and nano/ microstructured composites. [31][32][33][34][35][36] In addition, the huge volume expansion of anodes can also be accommodated through the ingenious introduction of void space in nanostructures of yolkshell, 37,38 hollow nanospheres, [39][40][41][42] and porous materials.…”
Section: Introductionmentioning
confidence: 99%